2019
DOI: 10.1111/jcpt.13098
|View full text |Cite
|
Sign up to set email alerts
|

Limited sampling strategy for predicting isoniazid exposure in patients with extrapulmonary tuberculosis

Abstract: What is known and objective: Limited sampling strategies (LSS), using few sampling times after dosing, have been used to reliably predict the isoniazid area under the 24hour concentration-time curve (AUC). Experience with isoniazid is very limited, and no LSS has been developed in south-Mediterranean populations. Hence, we aimed to develop an accurate and convenient LSS for predicting isoniazid AUC in Tunisian patients with extrapulmonary tuberculosis. Methods: Pharmacokinetic profiles consisting of six blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Limited sampling strategy models, based on multiple linear regression (MLR) or maximum a posteriori (MAP) analysis, were established for the estimation of AUC in patients who were administered INH. Alshaikheid et al (2020) established an LSS model, based on 25 patients using the MLR analysis. They found that C 3 , C 2 -C 6 , C 0 - C 1 -C 6 are suitable for estimation of INH AUC 0–24h .…”
Section: Discussionmentioning
confidence: 99%
“…Limited sampling strategy models, based on multiple linear regression (MLR) or maximum a posteriori (MAP) analysis, were established for the estimation of AUC in patients who were administered INH. Alshaikheid et al (2020) established an LSS model, based on 25 patients using the MLR analysis. They found that C 3 , C 2 -C 6 , C 0 - C 1 -C 6 are suitable for estimation of INH AUC 0–24h .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we chose C 3 as our monitoring point, as it was demonstrated in the study by Vivien and Thibier 8 that this sample time point is an excellent correlation with isoniazid total exposure and could be considered a good marker in isoniazid TDM. Furthermore, a limited sampling strategy developed by our team for predicting isoniazid exposure in patients with extrapulmonary TB demonstrated that a 1‐time‐point limited sampling strategy including C 3 had an acceptable correlation coefficient ( r ² = 0.9) 17 . As mentioned, most C 2 studies use a range of 3 to 5 µg/mL.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, a limited sampling strategy developed by our team for predicting isoniazid exposure in patients with extrapulmonary TB demonstrated that a 1-time-point limited sampling strategy including C 3 had an acceptable correlation coefficient (r 2 = 0.9). 17 As mentioned, most C 2 studies use a range of 3 to 5 μg/mL. However, it has also been suggested that a concentration of 1.5 μg/mL at the third hour is an optimum effective amount of drug against mycobacteria 9 and that a cutoff value of C 3 >3.69 μg/mL is associated with isoniazid-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, estimating the AUC requires several blood samples and could, therefore, be impractical in routine practice. C3 was selected for use in this study as it has been demonstrated that this sample time point has excellent correlation with INH total exposure, and could be considered a good marker in INH TDM (Vivien et al, 1973;Alshaikheid et al, 2020). Modelling of INH exposure using single time point concentration data alone has been performed in one previous study (Jung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%